Characterization of Covalently Bound Anti‐Human Immunoglobulins on Self‐Assembled Monolayer Modified Gold Electrodes. Issue 11 (5th June 2017) - Holzer, Brigitte; Manoli, Kyriaki; Ditaranto, Nicoletta; Macchia, Eleonora; Tiwari, Amber; Di Franco, Cinzia; Scamarcio, Gaetano; Palazzo, Gerardo; Torsi, Luisa
Abstract: Bioconjugated gold surfaces constitute interesting platforms for biosensing applications. The immobilization of antibodies such as anti‐immunoglobulin G and M (anti‐IgG and anti‐IgM) on gold electrodes via self‐assembled monolayers (SAMs) is here studied as a model system for further immunoassays development. The biolayer is characterized by means of X‐ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), a dedicated thin‐film transistor (TFT)‐based platform and electrochemical surface plasmon resonance (EC‐SPR). XPS analysis confirms the presence of all the chemical species involved in the fabrication process as well as the covalent attachment of the antibodies with high reproducibility. Visualization of the biolayer topography by AFM shows nanostructures with a thickness consistent with the actual size of the protein, which is also verified by SPR measurements. EC‐SPR allows taking advantage of complementary electrochemical and optical signals during the functionalization steps. Moreover, the functionalization of gold leads to a change in the work function, which is demonstrated in an electrolyte gated thin‐film transistor configuration. Such configuration enables also to evaluate the electrostatic changes occurring on the gate that are connected with the threshold voltage shifts. The data support that functional biomodified gold surfaces can be reproducibly prepared, which is a prerequisite for further biosensor development. Abstract : The immobilization of anti‐immunoglobulin G and M on gold electrodes via self‐assembled monolayers is studied as a model system for further immunoassays development. The biolayer is characterized by means of X‐ray photoelectron spectroscopy, atomic force microscopy, a dedicated thin‐film transistor‐based platform, and electrochemical surface plasmon resonance.